THE STUDY OF MISREPRESENTED HADITHS ON THE INTERNET ABOUT MUSLIM AND NON-MUSLIM RELATIONSHIPS - Haq, Ahmad Yusronil (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2023)
Relations between Muslims and Non-Muslims are often tinged with negative issues for various reasons and in various aspects. And this understanding circulates on the internet network which is easily accessible by the public, such as al-ahkam.net, markazsunnah.com, dan nisa-assunnah.com. But his explanation contradicts the meaning of the Qur'an and authentic Hadith. This research will discuss three hadiths about the relationship between Muslims and non-Muslims that are misunderstood in that three internet networks. The data are read according to hadith science standards which include assessing the quality of hadith, understanding the content of hadith through the fiqh al-hadith approach from the perspective of Yusuf al-Qaradawi, Muhammad al-Ghazali, and Ali Mustafa Yaqub, and supported by the views of other ulama regarding this discussion. This research shows that: (1) Hadith